Green Consumers Behavior: Perilaku Konsumen dalam Pembelian Produk Ramah Lingkungan - Kristiana Sri Utami (Jurnal Maksipreneur, 2020)
The government's concern in solving environmental problems is manifested by the launching of an environmental development program. The success of this program is highly influenced by people's behavior in choosing and consuming environmentally friendly products (also known as green consumers’ behavior). This study aims to examine the effects of environmental knowledge, environment attitude, recycle behavior, and political action on green consumers’ behavior in Yogyakarta Special Province, Indonesia by using a quantitative descriptive analysis of a sample of 100 respondents who were randomly selected. The type of data used in this research is primary data. The research variables consist of a dependent variable, namely green consumers’ behavior (GCB), and independent variables, namely environmental knowledge, environment attitude, recycle behavior, and political action. The data is processed and analyzed using the Statistical Package for the Social Sciences (SPSS) version 24. The method of this analysis used multiple linear regression. The analysis results showed that environmental knowledge and environment attitudes have not significant effects on green consumers’ behavior. While recycling behavior and political action have positive and significant effects on green consumers’ behavior.